2003
DOI: 10.1677/joe.0.1760285
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of mannose receptor/terminal high-mannose type oligosaccharide on osteoclast precursors during osteoclast formation

Abstract: Osteoclasts are formed from hematopoietic precursors via cell-cell fusion. We have previously reported that mannose residues are expressed on the outer membranes of monocytes during osteoclast differentiation. In the present study, we have attempted to demonstrate the pattern of expression levels of terminal high-mannose type oligosaccharide and to show that the mannose receptor is expressed on osteoclast precursor cells. Osteoclasts were formed using three different systems, namely mouse bone marrow cell cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…Other cells, isolated from bone marrow, lymph nodes, and spleen, showed various degrees of MMR expression levels corresponding to what has been described before (12,(34)(35)(36). Osteoclast cells that were generated in vitro stained positively for MMR, and these data are in line with findings reported by Morishima et al (15). However, in comparison with mature macrophages, the expression was only modest on osteoclasts; therefore, we concluded that MMR was not an ideal marker for this population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Other cells, isolated from bone marrow, lymph nodes, and spleen, showed various degrees of MMR expression levels corresponding to what has been described before (12,(34)(35)(36). Osteoclast cells that were generated in vitro stained positively for MMR, and these data are in line with findings reported by Morishima et al (15). However, in comparison with mature macrophages, the expression was only modest on osteoclasts; therefore, we concluded that MMR was not an ideal marker for this population.…”
Section: Discussionsupporting
confidence: 90%
“…Among the infiltrating cells in synovial tissues and fluid, macrophages constitute a subset of cells that differentiate into multinuclear osteoclasts, which are responsible for bone destruction in RA (32,33). In the present study, we imaged in an animal model of RA the distribution of MMR, a marker expressed by a subpopulation of macrophages and by osteoclasts (14,15). In our study, we confirmed the presence of macrophages in synovium and synovial fluid of arthritic mice.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…4) (40). More generally, high mannose glycans are not commonly observed on the surfaces of mammalian cells (41), with the exception of macrophages (42). High mannose glycans are involved in initial steps in N-glycan processing and control of protein folding in the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, investigations of the role of high mannose glycans have been mostly directed to their involvement in initiating the innate immune system or in protein folding in the endoplasmic reticulum. A few studies, however, have suggested that high mannose glycans mediate cell-cell fusion (42,44), mediating sperm-egg fusion, myoblast fusion, and osteoclast formation. Thus, high mannose glycans on hESCs may play a role in cellular binding and recognition.…”
Section: Discussionmentioning
confidence: 99%